Gaseous discharge plasma switching in oversized interference microwave switches; Journal of Physics: Conference Series; Vol. 1393 : Gas Discharge Plasmas and Their Applications (GDP 2019) - Artemenko S. N. Sergey Nikolaevich; Gorev S. A. Stanislav Andreevich; Igumnov V. S. Vladislav Sergeevich; Novikov S. A. Sergey Avtonomovich; Yushkov Y. G. Yuri Georgievich (2019, 2019)
Title screen